Production, composition and fatty acid profile of milk and butter texture of dairy cows fed ground or pelleted concentrate with sunflower and/or lignosulfonate - Fábio José Ferreira Figueiroa (Revista Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate the milk production, composition, milk fatty acid profile, butter texture and blood parameters of Holstein cows fed corn silage and concentrate containing one of the following: ground sunflower seeds; ground sunflower seeds treated with 50 g of lignosulfonate/kg of sunflower dry matter; pelleted sunflower seeds; or ground sunflower seeds pelleted and treated with 50 g of lignosulfonate/kg of sunflower dry matter. Four lactating cows were used, each with 130±28 days in lactation and a body weight of 569±63 kg. These animals were distributed in a Latin square design with four periods of 21 days each, with 14 days of adaptation and seven days of data collection. The diets were formulated to meet nutritional requirements and had a forage:concentrate ratio of 60:40. The milk fat was lower in the pelleted treatments. The concentrations of 16:1 n-11 and trans18:1 n-9 in the milk increased, and the n-6:n-3 ratio was higher for the pelleted treatments. The firmness and adhesiveness of the butter and the blood parameters analyzed were not affected by the treatments. Addition of lignosulfonate is not effective in protecting polyunsaturated fatty acids from the ruminal biohydrogenation process, and the pelleting process has little effect on the milk fatty acid profile and can not change the butter texture.